Strategi pemasaran politik pasangan Ikfina-Barra dalam kontestasi Pilkada Kabupaten Mojokerto tahun 2020 - Elis Mardianti (Universitas Airlangga, 2024)
The Ikfina-Barra pair in the 2020 Mojokerto District Election contested won with a total of 62.5% of the total valid votes. This study aims to identify and describe the political marketing strategy of the Ikfina-Barra pair in the 2020 Mojokerto District Election contest. Through the use of descriptive descriptive research methods, data collection techniques were carried out through a process of in-depth interviews, observation, and documentation. Data analysis techniques in this study include the process of reducing data, presenting data, and drawing conclusions and verification. This study uses the political marketing model of Bruce I. Newman to analyze it. The results of this study indicate that the Ikfina-Barra pair used a political marketing strategy by carefully dissecting the entire mix as well as using a political marketing strategy with a humanist approach and targeting a psychological approach to the people of Mojokerto Regency. In the candidate focus mix, the nomination of the Ikfina-Barra pair shows the presence of a candidate focus on the marketing concept where the Ikfina-Barra pair is a candidate pair requested by the community by the Mojokerto Regency through a grassroots survey. Then in marketing campaign mix, the Ikfina-Barra pair used segmentation and positioning strategies for the effectiveness of political campaigns by approaching voters and offering political products according to predetermined segments. In the process of formulating and implementing a political marketing strategy, the Ikfina-Barra pair fully used the 4P mix conceptualized by Bruce I. Newman namely Product, Push Marketing, Pull Marketing, and Polling. An interesting finding in this study is that the Ikfina-Barra pair also used the Pass Marketing strategy in the marketing campaign process. In addition, in the entire process of political marketing that was carried out, the Ikfina-Barra pair also conducted an analysis of environmental forces to identify opportunities and challenges in the process of marketing campaigns and political campaigns.